Analisis Kadar Karbohidrat dan Lemak Keju Mozarella Menggunakan Metode Luff-Schoorl dan Weibull Berdasarkan SNI 01-2891-1992 - Reni Reni; Alizar Ulianas (MASALIQ, 2026)
Mozzarella cheese is a widely consumed dairy product and has distinctive characteristics, such as meltability and elasticity, which are influenced by its nutritional composition, particularly carbohydrate and fat content. Nutritional content analysis of mozzarella cheese is important to ensure product quality and its conformity with food standards. This study aims to determine the carbohydrate and fat content of mozzarella cheese based on the SNI 01-2891-1992 method. Carbohydrate content was determined using the Luff-Schoorl method, while fat content was analyzed using the Weibull hydrolysis method. The mozzarella cheese samples were prepared through dissolution and hydrolysis processes before testing. The analysis results showed that the carbohydrate content in the mozzarella cheese sample was 1.8778%, while the fat content was 24.4548%. The low carbohydrate content indicates that most of the lactose had undergone fermentation during the cheese-making process. Meanwhile, the fat content obtained met the quality requirements for mozzarella cheese based on SNI 8896:2020, namely a minimum of 18%. Thus, the Luff-Schoorl and Weibull hydrolysis methods can be used to accurately determine carbohydrate and fat content in mozzarella cheese in accordance with the Indonesian National Standard (SNI).